SERANGAN BOKTOR (Xystrocera festiva Pascoe) DAN KARAT TUMOR (Uromycladium tepperianum (Sacc.) McAlpine) PADA SENGON (Falcataria mollucana (Miq.) DI PERKEBUNAN TEH CIATER - Wida Darwiati Jusuf; Illa Anggraeni (Universitas Nusa Bangsa, 2018)
Sengon has become one of the preferred tree because it has many advantages over other commercial tree species. It was widely cultivated with a monoculture system, like agricultural cultivation. The consequence of monoculture planting system was the unstable microclimate environment, so the ecosystem was susceptible to the pest and disease explosion. As happens at the Ciater plantation site, sengon plants were attacked by pests and diseases. The purpose of research were to study the extent data and intensity of boktor pests and tumor rust disease, boktor pest and bioecological behavior causing tumor rust on sengon as a protective and shade plant. The percentage and intensity of attacks caused by boktor pests and tumor rust disease was relatively high. The lowest percentage of boktor attacks was 40% and the highest was 90%. It could be categorized as serious severity, even dead plants. The percentage and intensity of the attacks indicated that the pests living on sengon could thrive in suitable food sources. Likewise with the percentage and intensity of attacks caused by rust disease has reached 100%, so it could be categorized as the level of damage was high.Keywords: boktor pests, intensity of attack, percentage, sengon, tumor rust disease . ABSTRAK Sengon salah satu pohon yang memiliki banyak keunggulan dibandingkan jenis pohon lainnya dan banyak dibudidayakan secara luas dengan sistem monokultur seperti budidaya pertanian. Konsekuensi sistem tanam monokultur adalah lingkungan mikroklimat yang tidak stabil, sehingga ekosistemnya rentan terhadap hama dan penyakit. Tujuan dari penelitian ini, untuk memperoleh data luas dan intensitas serangan hama boktor dan penyakit karat tumor, perilaku hama boktor dan bioekologi penyebab penyakit karat tumor pada sengon. Metode yang digunakan adalah pengamatan visual setiap tegakan yang terserang oleh hama boktor dan penyakit karat tumor. Persentase dan intensitas serangan akibat hama dan penyakit ini relatif tinggi, untuk hama boktor persentase dan intensitas terendah 40% yang tertinggi 90%, sehingga dapat dikategorikan tingkat keparahan berat, bahkan ada tanaman yang mati. Persentase dan intensitas serangan tersebut menunjukkan bahwa hama yang hidup pada tegakan sengon berkembang dengan sumber makanan yang cocok. Begitu juga dengan persentase dan intensitas serangan akibat penyakit karat tumor sudah mencapai 100%, sehingga dapat dikategorikan tingkat keparahan yang tergolong berat. Kata Kunci : boktor, intensitas serangan, karat tumor, persentase serangan, sengon.